2021
DOI: 10.4103/jomfp.jomfp_232_20
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscope characterization of noncarious cervical lesions in human teeth

Abstract: Aims: Abfraction is a theoretical process whereby occlusal forces create microfractures in enamel and dentin along the cervical area and predispose it to erosion and abrasion, forming noncarious cervical lesions. However, the theory is not yet proven. The aim of this study was to elucidate the role of abfraction as an etiology of these lesions. Materials and Methods: Ten human premolars with these lesions from 10 patients requiring tooth extraction, one tooth from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The location of the abfraction lesions is mainly in the cervical area of the teeth [20] , sometimes the patient feels sensitivity [21] . It is characterized by crack-like lesions [3] , with sharp internal and external line angles [22] horizontal striae [11] , plate-like lesions located at enamel level, crescent-shaped lesions [23] , depression at the cusp tip in premolars and molars [4] , the shape and size of the lesion depending on the direction, magnitude, frequency, duration and location of the forces that arise when the teeth come into contact [22] . Since ancient times, they concluded that carious lesions were found near the point of support where there was a greater concentration of traction stress.…”
Section: Clinical Aspectmentioning
confidence: 99%
See 2 more Smart Citations
“…The location of the abfraction lesions is mainly in the cervical area of the teeth [20] , sometimes the patient feels sensitivity [21] . It is characterized by crack-like lesions [3] , with sharp internal and external line angles [22] horizontal striae [11] , plate-like lesions located at enamel level, crescent-shaped lesions [23] , depression at the cusp tip in premolars and molars [4] , the shape and size of the lesion depending on the direction, magnitude, frequency, duration and location of the forces that arise when the teeth come into contact [22] . Since ancient times, they concluded that carious lesions were found near the point of support where there was a greater concentration of traction stress.…”
Section: Clinical Aspectmentioning
confidence: 99%
“…Abfraction is the loss of dental tissue [1] that is independent of the bacterial process [3] . These lesions are very common and frequently require treatment in clinical practice [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once tooth decay is ruled out as the origin of this condition, other factors involved must be recognized. The multifactorial origin manifests with combinations of distinct processes, including stress (abfraction), mechanical wear (abrasion), and biocorrosion (erosion) [1,3,[9][10][11][12]. Studies indicate that due to noncarious cervical lesions together with dental decay, restoration of permanent teeth is needed [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the specialized literature, there are studies on the morphology, etiology and evolution of NCCLs using various methods of investigation, among which we mention the following: the optical coherence tomography method (OCT) [20][21][22], micro-computed tomography [23,24], and electron microscope examination [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%